FLUOROQUINOLONE-RESISTANT UNCOMPLICATED URINARY TRACT INFECTIONS, CHINESE HERBAL MEDICINE MAY PROVIDE HELP - Tong, Yanqing; Jing, Yue; Zhao, Dongkai; Zhang, Liping; Zeng, Shiming (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
We assessed the effects of Chinese herbs on the uncomplicated urinary tract infections (UTIs) in women caused by fluoroquinolone-resistant strains. A total of 56 pre-menopausal women with uncomplicated UTIs caused by fluoroquinolone-resistant strains were included. Urine cultures were carried out. All organisms were proved to be fluoroquinolone-resistant at baseline. The patients were orally administrated Chinese herbal concoction for ten days. Chinese herbal concoction eradicated the primary pathogen in 71.4% of the patients at the 1-week follow-up. Among the 20 patients who had bacteriologic failures in the Day 5 of treatment, 2 developed superinfection. Of the failures in the group, Proteus mirabilis, Staphylococcus epidermidis and Providencia rettgeri were implicated in 50.0%, 50.0% and 100.0% of the failures, respectively. The clinical outcomes were also good, with cure or improvement for more than 80% of all subjects. About 14% of the study subjects reported at least one potential adverse event. The adverse events most frequently reported were nausea and diarrhea. All patients tolerated the symptoms. The adverse reactions did not prevail after discontinuation of the medication. Chinese herbal therapy may be an acceptable alternative for the treatment of uncomplicated UTIs caused by fluoroquinolone-resistant uropathogens.